Finite element analysis and optimization of an electric bicycle frame (2024)
This personal project investigates the failure mechanisms and structural integrity of a Colombian electric bicycle frame through Finite Element Analysis (FEA). The primary objectives are to determine the cause of failure at a specific point in the frame, document operational and environmental conditions affecting its structural integrity, analyze the materials used in its manufacture, and evaluate the original design for potential deficiencies. The software used to carry out the analysis was ANSYS and the software used to create all the computer aided designs (CAD’s) was Autodesk Fusion 360. Simulations revealed that horizontal impact is a significant factor contributing to frame failure, with stress concentrations exceeding the ultimate tensile strength of the material. Operational conditions, such as weight distribution and impact scenarios, were documented, highlighting their impact on frame durability. Material analysis indicated that carbon steel AISI 1020, while generally within the elastic region under normal conditions, is prone to fatigue over time. The original design exhibited high-stress areas, particularly near the pedals and the seat joint, suggesting the need for redesign. Recommendations for improvement include reinforcing critical joints, optimizing material use, and eliminating unnecessary supports to reduce weight and enhance performance. An alternative design was proposed, incorporating insights from market research and advanced simulation data. The new design aims to provide a stronger, more reliable frame by addressing the identified weaknesses and leveraging topological optimization. Continued testing and refinement will ensure that the new frame design meets the highest standards of safety and functionality, offering riders a high-performance, durable product. This research provides a comprehensive understanding of the factors affecting bicycle frame integrity and proposes practical solutions for future design improvements.